Triple Procedure for Dense Cataractous Neovascular Glaucoma Patients - Hossam M. Moharram; Shaaban Abd-Elhamid Mehany Elwan; Mahmoud M. Nassar; Mohamed F. Abdelkader (Journal of Ophthalmology)
Purpose. One of the most difficult refractory glaucomas is the neovascular type (NVG), and its association with dense cataract adds to this difficulty. This study aimed to provide results of the triple surgical procedure for such conditions. Methods. 12 eyes of 12 patients with NVG and dense cataract were included in this case series study. The mean age of patients was 57.25 ± 5.9 years. The mean preoperative intraocular pressure (IOP) was 47.25 ± 4.04 mmHg with maximum antiglaucoma therapy. The mean best corrected distant visual acuity (BCDVA) in LogMAR was 2.13 ± 0.38. All patients received intravitreal injection of 1.25 mg (0.05 ml) bevacizumab followed by phacoemulsification, pars plana vitrectomy (PPV) including panretinal photocoagulation (PRP), and trabeculectomy with mitomycin C (MMC). Mean IOP and BCDVA changes were the main outcome results of this study. Results. The follow-up period was 2 years. The mean BCDVA was improved to 1.22 ± 0.35, 1.13 ± 0.34, 1.12 ± 0.37, 1.06 ± 0.38, and 1.01 ± 0.37 at 1, 3, 6, 12, and 24 months, respectively, after this procedure. This improvement was statistically significant when compared with preoperative BCDVA (P<0.0001). The mean postoperative IOP was dropped to 20.08 ± 4.1, 17.08 ± 2.1, 17.17 ± 5, 15.75 ± 4.7, and 16.17 ± 6.1 mmHg, respectively. At the last follow-up, the mean IOP was statistically significantly lower than preoperative IOP (P<0.0001) at the previously mentioned time points. The success rate was complete in 90.9% of eyes and qualified in 100% of eyes. Iris and angle neovascularization had regressed significantly in all patients, and no serious complications occurred during the follow-up period. Conclusions. This triple surgery can safely improve patients with NVG and dense cataract regarding BCDVA and IOP control. This trial is registered with NCT04143620.